Risk Factor Analysis Of Dengue Fever In Indonesia: Literature Review - Bambang Irawan; Zahratul Hayati (Jurnal EduHealth, 2023)
Dengue Hemorrhagic Fever (DHF) is an acute infectious disease caused by the dengue virus. Based on WHO data, it is estimated that every year around 50-100 million people are indicated to be infected with the dengue virus. This study aims to determine the factors that can influence the increasing number of cases of Dengue Hemorrhagic Fever in Indonesia based on a literature review. This study used a descriptive method with a literature review approach. This study uses previous studies with the criteria of being indexed by Sinta 2, 3, 4 and 5 and the maximum publication time of the last 5 years. The results showed that there were several factors that caused the incidence of DHF, namely water reservoirs, garbage collection, the habit of hanging clothes, the use of mosquito repellents,